Russell's logical atomism - Bostock, David (Oxford : Oxford University Press, 2012)
David Bostock presents a detailed account and critical appraisal of the development of Bertrand Russell's philosophy from 1900 to 1924. He explores Russell's logical atomism, which applies logic to problems in the theory of knowledge and metaphysics and was central to Russell's work over this period.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references and index.
Keywords: Russell, Bertrand, -- 1872-1970.; Logical atomism